The effects of chondroitin sulfate supplementation on indices of muscle damage induced by eccentric arm exercise - Braun, W. A.; Flynn, M. G.; Armstrong, W. J.; Jacks, D. E. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: Delayed onset of muscle soreness (DOMS) often results from unaccustomed exercise or exercise that involves heavy eccentric loading of skeletal muscle. Chondroitin sulfate (CS) has been reported to possess anti-inflammatory and analgesic properties and has been used widely in the treatment of osteoarthritis. Based on these findings, the investigators sought to determine whether CS supplementation might reduce DOMS symptoms associated with eccentric arm exercise. Methods: Sixteen non-resistance-trained males participated in a double-blind protocol. Subjects consumed 3 600 mg·day-1 of encapsulated CS or placebo for 14 days preceding the exercise protocol and during 48 hours of follow-up measurements. Subjects performed a maximum of 50 eccentric contractions of the elbow flexors against a resistance that was 120% of the concentric one-repetition maximum. Results: Significant time effects were present for soreness, relaxed elbow extension (joint angle), and creatine kinase; all measures were significantly altered 48 hours after the exercise session. No effects were present for complement system fragment C3a and prostaglandin E2. No significant treatment or interaction effects were detected for any of the variables. Conclusion: CS supplementation was not found to be effective in the prevention of DOMS, nor did it influence biochemical indices of inflammation and muscle damage following heavy eccentric loading of the arm flexors.